Mood Effects on Stereotype-Based Conjunction Probability Judgments of Minorities in Education. - Lieberman, Emma R. (Tufts Archival Research Center, 2014)
Abstract: Previous research has proven people commit the conjunction fallacy because of stereotype-use. Additionally, previous research has demonstrated that mood effects stereotype-use. The current study investigates mood effects on stereotype-based conjunction probability judgments under the classical and quantum probability theory. Forty undergraduate participants were randomly assigned to either a sad or neutral mood condition. All participants then answered 32 questions about the probabilities of individuals from difference races and genders experiencing adverse educational outcomes. The results show individuals committed the conjunction fallacy for minority females when under the sad mood condition. Also, individuals tended to commit the conjunction fallacy for minority males when they were under the sad mood condition. There were close to significant results for differences in mood conditions of participants when they made probability judgments about minority females and white females. Lastly, individuals tended to make higher probability judgments under the sad mood condition than under the neutral mood condition. Stereotype-use was demonstrated and the conjunction fallacy was committed. The present results are more consistent with the stereotype-use explanation of the conjunction fallacy.